Waterborne hyperbranched alkyd-acrylic resin obtained by miniemulsion polymerization (2016)
Four waterborne hyperbranched alkyd-acrylic resins (HBRAA) were synthesized by miniemulsion polymerization from a hyperbranched alkyd resin (HBR), methyl methacrylate (MMA), butyl acrylate (BA) and acrylic acid (AA), by using benzoyl peroxide (BPO) and ammonium persulfate (AP) as initiators. The reaction between HBR and acrylic monomers was evidenced by differential scanning calorimetric (DSC), nuclear magnetic resonance (NMR) and gel permeation chromatography (GPC). The conversion percentage, glass transition temperature (Tg), content of acrylic polymer (determined by soxhlet extraction) and molecular weight increased with the content of acrylic monomers used in the synthesis. The main structure formed during the synthesis was the HBRAA. The analysis by dynamic light scattering (DLS) showed that the particle size distribution of HBRAA2, HBRAA3 and HBRAA4 resins were mainly monomodal. The film properties (gloss, flexibility, adhesion and drying time) of the HBRAA were good.